Tantangan Demokrasi di Minangkabau dan Falsafah Bulek Aia Dek Pambuluah Bulek Kato Dek Mufakaik - Diana Yualiska; Hasrul Hasrul; Yusnanik Bakhtiar; Muhammad Prima Ersya (Journal of Civic Education, 2022)
This study explores the difficulties encountered in the implementation of the Bulek Aia Dek Pambuluah Bulek Kato Dek Mufakaik philosophy as a manifestation of democracy in Minangkabau. In the era of globalization, the democratic system in Minangkabau society has undergone significant changes. The study employed a qualitative approach, with ninik mamak at KAN Salapan Padang and the people of North Padang, where KAN Salapan was located, being interviewed. Data analysis involved techniques such as data reduction, data presentation, and drawing of conclusions. The findings indicate that the current challenges of implementing democracy in Minangkabau include the existence of a voting system and low levels of community participation in decision-making. These are indirectly influenced by globalization and changing times. One limitation of this study is that it does not examine the efforts made by KAN Salapan in confronting these challenges.